The Cultural Treasures Of Kampung Bugis In The Customary Village Of Serangan, Denpasar - Segara, I Nyoman Yoga (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2018)
Kampung Bugis is a small community of Bugis people who occupy a special land in the customary village of Serangan. The oral narrative stated that the village was a gift from the King of Pamecutan Badung in regard for their merits in assisting the kingdom during the war. They were eventually known as hard workers, courageous, and immigrants like the Bugis people in general. They also bring those sets of attitude to overseas, one of them in the customary village of Serangan, Denpasar. In addition to being able to adapt very well, they were also capable of maintaining a religious life in harmony with the society of Serangan where the major religion was Hindu. In 2007, the village of Kampung Bugis experienced a tragedy of eviction that eliminated half of the village. During the evictions they also survived by continuing the tradition and caring for the heritage of their noble cultural treasures through the old As Syuhada mosque, the old Qurâan book, the historical old tomb, and Bugis typical stage house. This writing is to highlight the cultural treasures and tradition that the people of Bugis strive for despite of many unfortunate events they experience including the recent evictions. Keywords: Bugis Village, the Customary Village of Serangan, As-Syuhada Old Mosque, Qurâanic Book, Old Tomb, Bugis Typical Stage House.